Coping with Teaching and Learning Creative Arts in Malaysian Public Universities in The Time of Covid-19 Pandemic - Lim, Connie Keh Nie; Yow, Chong Lee; Chow, Ow Wei (Human Resource Management Academic Research Society, 2020)
The unprecedented COVID-19 pandemic has disrupted the operation of Malaysian public universities and infinitely affected the way academics work. It is a devastating challenge where academics in the field of creative arts strived to cope with a transition from shifting face to face studio-based teaching and learning activities to online teaching and mentoring. This gave rise to a sudden change for them to carry out their administrative duties full-time at home and to re-adjust to alternative academic activities during the cordon sanitaire. This article describes the experiences and unusual situations faced by the academics, as well as their responses to this crisis in different dimensions starting from the initial stage of the Movement Control Order until the period they resumed work in the university office. The discussion proceeds with how the global pandemic has affected their teaching routine in the field of creative arts at present with a focus on music and film specialisations. This phenomenon-derived ethnography significantly employs self-conscious observation along the online teaching process uniquely conducted for a few respective courses in designated Malaysian public universities when the pandemic-triggered disruption was experienced. With a discussion only limited to observation based on the data gathered for the teaching component, the authors hope to recommend a practical approach in reinvigorating academic practices during and post COVID-19 period.